Biathlon shooting training with scatt-simulator - accuracy shooting training of young biathletes - Plotskaya, E.; Zakharova, A. (Proceedings of the 3rd International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2015)
Teaching marksmanship to beginners in biathlon is extremely difficult. The usage of SCATT shooting simulator system, its software and shooting parameters interpretation are under consideration. Methods. A group of 12 well-trained young biathletes (6 males and 6 females), 14-19 years old, with 3-5 years of training experience in skiing and biathlon were recruited as participants. Every athlete had 0.5 hours of SCATT-shooting 3 times per week. Each athlete`s shooting parameters were measured on the 1st, 10th, 18th and 21st days of our experiment. Results. Novices in shooting decreased the average aiming trajectory length "L" from 434 ± 39 mm to 370 ± 65 mm and improved the graph "Coordination" line and its location within the target zone in biathlon standing shooting. The average shooting "Result" was 4.5±1.08 in novices (enough for biathlon standing shooting). All young biathletes with 3-5 years of shooting experience corrected the shooting aiming errors. The dynamics of "L" is indivi dual and too dependent on the athlete`s fatigue degree.